2016
DOI: 10.1007/s00109-016-1488-y
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic potential of pro-angiogenic BPC157 is associated with VEGFR2 activation and up-regulation

Abstract: BPC 157 promotes angiogenesis in CAM assay and tube formation assay. BPC 157 accelerates the blood flow recovery and vessel number in rats with hind limb ischemia. BPC 157 up-regulates VEGFR2 expression in rats with hind limb ischemia and endothelial cell culture. BPC 157 promotes VEGFR2 internalization in association with VEGFR2-Akt-eNOS activation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
140
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 66 publications
(144 citation statements)
references
References 41 publications
4
140
0
Order By: Relevance
“…BPC 157 reduces high myeloperoxidase (MPO) activity in colonic tissue (Veljaca et al., ), and in particular, heals fistulas (Baric et al., ; Grgic et al., ; Klicek et al., ), rescues failed anastomosis healing (Klicek et al., ; Sever et al., ; Vuksic et al., ), and markedly improves intestinal adaptation following massive bowel resection (Sever et al., ). Studies have shown different molecular mechanisms involved in BPC 157 beneficiary effects (Chang et al., , ; Hsieh et al., ; Huang et al., ). Thus, recently the increased expression and internalization of VEGFR2, and the activation of the VEGFR2‐Akt‐eNOS signaling pathway have been implicated (Hsieh et al., ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…BPC 157 reduces high myeloperoxidase (MPO) activity in colonic tissue (Veljaca et al., ), and in particular, heals fistulas (Baric et al., ; Grgic et al., ; Klicek et al., ), rescues failed anastomosis healing (Klicek et al., ; Sever et al., ; Vuksic et al., ), and markedly improves intestinal adaptation following massive bowel resection (Sever et al., ). Studies have shown different molecular mechanisms involved in BPC 157 beneficiary effects (Chang et al., , ; Hsieh et al., ; Huang et al., ). Thus, recently the increased expression and internalization of VEGFR2, and the activation of the VEGFR2‐Akt‐eNOS signaling pathway have been implicated (Hsieh et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown different molecular mechanisms involved in BPC 157 beneficiary effects (Chang et al, 2011(Chang et al, , 2014Hsieh et al, 2017;Huang et al, 2015). Thus, recently the increased expression and internalization of VEGFR2, and the activation of the VEGFR2-Akt-eNOS signaling pathway have been implicated (Hsieh et al, 2017). However, further studies will be needed to designate these effects to the affected honeybee midgut.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a study conducted by Hsieh et al (2017), the authors aimed to explore the proangiogenic and therapeutic effect of BPC 157. Demonstrated by chick chorioallantoic membrane (CAM) and endothelial tube formation assays, both in vivo and in vitro, BPC 157 was shown to increase both vessel density and accelerate the recovery of blood flow in ischemic muscle, indicating a promotional effect on angiogenesis.…”
Section: Prolonged Therapeutic Benefitsmentioning
confidence: 99%